Rancang Bangun Sistem Tracer Study Pada Program Studi Sistem Informasi Universitas Peradaban Berbasis Website Menggunakan Metode Unified Process - fajrian, Melly Ayu; Mukrodin, Mukrodin; Yudhistira, Yusuf (Jurnal Sistem Informasi dan Teknologi Peradaban, 2024)
Peradaban University is one of the tertiary institutions in Brebes, precisely in the Bumiayu area. Currently, Peradaban University has conducted a Tracer Study using an online system, namely by filling out a questionnaire form via Google Form and processing it using Microsoft Excel. One of the drawbacks of using the Google form is when alumni fill in incorrectly and automatically have to fill it in which results in information piling up and less effective. This of course made it difficult for the Tracer Study team and required a long time in the process of tracing alumni. By looking at these needs, the authors designed a Tracer Study system that would assist in the process of gathering information related to alumni. The research method used by the author is Unifield Process, the programming language used is PHP with the Laravel framework. The database design used by the author is Entity Relationship Diagram (ERD). In the material conceptual design program the author uses the Unifield Modeling Language (UML), including Use Case Diagrams and Class Diagrams. The purpose of creating a Tracer Study system is to facilitate data collection and the process of finding graduates or alumni. The results of this study are to make it easier for alumni and stakeholders to fill out questionnaires so that the tracer team gets valid feedback results and makes reports better.Keywords : Tracer Study, Framework Laravel, Unifield Process, Mysql.